(untitled) (PerCursos, 2023)
This paper presents theoretical and empirical reflections on the role of collective subjects of urban struggles in the Metropolitan Region of Rio de Janeiro (RMRJ) in understanding the militarization of cities as a state policy. The premise is that the militarization of cities is an expression of the contemporary urban question, as well as part of the dynamics of capital accumulation in and through the appropriation of urban space. These reflections are situated in the field of studies on social movements that problematize the subject-object relationship and consider collective subjects as holders of political knowledge relevant to the defense of the right to the city for the construction of a project of democratic society.